Current research trends in the process of using zeotropic mixtures in energy installations; Lorenz’s comparative cycle - Kruzel, Marcin; Bohdal, Tadeusz; Dutkowski, Krzysztof (Instal, 2023)
This paper is devoted to modern research directions and the development of the use of zeotropic mixtures in compact heat exchangers presents selected problems regarding the use of zeotropic mixtures in the implementation of refrigeration cycles in heat pumps. The phenomenon of temperature glide occurring in phase transitions has a significant impact on the selection of an appropriate reference circuit. For homogeneous refrigerants and for azeotropic mixtures, the reference cycle is the Carnot cycle with constant source temperature levels. In the case of zeotropic mixtures, due to temperature glide, there is a system with variable values of the temperature of the heat sources, for which the Lorenz cycle is an appropriate pattern. The method of calculating the coefficient of performance of a heat pump operating according to such a cycle and the criteria for assessing the approximation of the real cycle to the model cycle is given.
Keywords: Temperature glide; Lorenz cycle; zeotropic mixtures; condensation; heat pumps; mixture composition